Rough sleepers [book club bag] - Kidder, Tracy (Random House, 2023)
"When he graduated from Harvard Medical School, Jim O'Connell was asked by the medical school Dean to spend one year setting up a program to care for the homeless population in Boston. It became Jim O'Connell's life calling, to help people known as "rough sleepers." For the past three decades, Dr. O'Connell has run the Boston Healthcare for the Homeless Program, which he helped to create. Affiliated with Massachusetts General Hospital, the program includes clinics and a van on which Dr O'Connell and his staff ride through the Boston streets at night, offering outreach of medical care, socks, soup, and friendship to a marginalized community"--